Genotype-Environment Interactions and Yield Stability of Cowpea (Vigna Unguiculata L. Walp) in Lomami Province, Central Part of Democratic Republic of Congo - Mukendi, Remy Tshibingu; Kayenga, Antoine Lubobo; Baboy, Louis Longanza; Bugeme, David Mugisho; Kalonji, Adrien Mbuyi; Munyuli, Théodore Mushambanyi (International Journal of Sustainable Agricultural Research, 2019)
The genotype environment interaction (GEI) has always been considered as an important issue by researchers involved in varietal selection and yield performance assessment. The objective of this study was to identify stable genotypes of cowpea in the Greater Kasai region. The current study was undertaken in 3 locations in the Ngandajika territory of Lomami Province (central part of Democratic Republic of Congo (DRC) with 12 improved cowpea genotypes obtained from the National Institute for Agricultural Research and Studies. The experiments were conducted following the randomized block design with 3 replicates and 12 treatments. Analysis of variance (ANOVA) and AMMI model were applied to identify main effects and GEI. The genotype yield stability across different locations was determined using the stability value of AMMI (ASV) rank of the AMMI model. ANOVA test indicated that there was performance inconsistencies in the yield of the 12 genotypes tried across the environments retained in this study. However, AMMI model revealed genotypes with stable yields across the different environment considered in the study. For the determination of the specificity of adaptability of genotypes to specific environments, the stability value of AMMI and diagram plot techniques were used for the discrimination of the genotypes versus the different environments considered. The genotypes Mujilanga (V2), CNGKASA7-2-M (V3) and CNGKASC2-1-1-T (V9) were identified as the most stable across different environments studied. Their yields were significantly higher (P<0.05) since they oscillated between 260 and 369 kg / ha as compared to the overall average of 312 kg / ha.